Implementation of a Web-Based Inventory Management Information System - Ani Yoraeni; Asima Margaret; Muhimatul Ifadah; Ade Mulyono (Komunitas Dosen Indonesia, 2025)
The use of internet technology in business processes is increasingly encouraging organizations to adopt digital systems that can improve operational efficiency and support data-driven decision-making. However, PT. Jodo Global still calculates inventory records manually, which causes data inconsistencies, loss of information, reporting delays, and limited inventory records. This problem indicates a significant research gap, as the lack of an integrated inventory system has significantly impacted operational accuracy and the effectiveness of managerial decision-making. This study aims to address these issues by developing a web-based inventory information management system capable of providing real-time stock monitoring, structured transaction recording, and automated report generation. The system was developed using a structured methodology encompassing requirements analysis, system design, implementation, and validation through black-box testing. The testing phase focused on evaluating the system's core functions such as stock updates, transaction recording, user authentication, and report generation-based on predetermined performance indicators, including accuracy, system responsiveness, and minimal functional errors. The results showed measurable performance improvements after the system was implemented. Inventory update processing time decreased by approximately 60%, recording errors were reduced by 83%, and the reporting process became fully automated, supporting faster and more reliable managerial decision-making. Overall, the system provides a scientifically proven digital solution that improves operational efficiency, accuracy, and productivity at PT. Jodo Global.